Folding pathway mediated by an intramolecular chaperone. - Shinde, U (1993)
The N-terminal propeptide of subtilisin, a serine protease, functions as an intramolecular chaperone which is crucial for proper folding of the active enzyme. This nascent N-terminal propeptide is removed after completion of the folding process. Here we present a possible pathway by which intramolecular chaperones mediate protein folding. Using circular dichroism to analyze acid-denatured subtilisin we have identified a folding-competent state which can refold to an active conformation in the absence of the propeptide. Earlier work had shown that guanidine hydrochloride-denatured subtilisin was in a state incapable of folding in absence of its propeptide. Comparison of the folding-incompetent and folding-competent states indicates that refolding is facilitated by the presence of residual structure present only in the folding-competent state. The analysis further indicates that the propeptide is essential for inducing this state. Therefore the folding-competent state may lie on--or be in rapid equilibrium with an intermediate on--the folding pathway of subtilisin. In the absence of the propeptide, formation of such a state--and hence refolding--is extremely slow.